We shall remain [videorecording (DVD)] : America through native eyes. After the Mayflower - Eyre, Chris, 1969-; Craig, Dustinn; Colt, Sarah; Nelson, Stanley, 1951-; Burns, Ric; Bratt, Benjamin, 1963- (American Experience, 2009)
"A groundbreaking mini-series and provocative multi-media project that establishes Native history as an essential part of American history. Five 90-minute documentaries spanning three hundred years tell the story of pivotal moments in U.S. history from the Native American perspective"--Series web site.